Student's guide to writing dissertations and theses in tourism studies and related disciplines - Coles, Tim (Routledge, 2013)
"Around the world every year many thousands of students have to complete dissertations or theses as part of their undergraduate or masters studies in tourism and related subjects. Often the dissertation or thesis represents the culmination of their programme as a substantial piece of self-directed work. More than just a means to consolidate their final grade, it is also an exciting chance to conduct intensive research on a topic of their choosing. It can also be a gateway to further periods of study as well as job offers and future career paths. Yet for all these reasons, the dissertation is viewed by many students as a tricky challenge. This book intends to take the stress and anxiety out of doing a dissertation in tourism studies and related disciplines. The dissertation process is examined from the germination of an idea to the submission, presentation and assessment of the final document. We offer a framework for conducting dissertations in the English-speaking world which students can adopt to varying degrees in their research at the undergraduate and masters levels. We aim to debunk the popular myths and common pitfalls of doing a dissertation. Rather than view the dissertation as a single, overwhelming project, the dissertation is presented as a series of more modest, manageable yet crucially inter-linked tasks that all students can successfully complete through effective time management"--